PEMIKIRAN SOSIAL BUDAYA IBN KHALDUN - Ainun Masnunah, Ahmad Hasanuddin, dan Neli Rahmah (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2022)
One of the figures of islamic philosophy who is considered to have different thought from other muslim philoshophers is Ibn Khaldun. Besides being famous as a muslim philoshopers , Ibn Khaldun is also known as the father of sociology, which in his thinking is widely recognized by western thinkers. The social-cultural view in Ibn Khaldun’s view says in hid Muqaddimah Ibn Khaldun that culture (Hadharah) is the cinditions of life that exceed what us needed by humans. This study aims to findout the substance of Ibn Khaldun’s thought on socio-culture, besides that it aims to see Ibn Khaldun’s thoughts on socio-culture to be transformed in the present. This research in in the form of library research. On the other hand, in collecting data trough the documentation process, then daya analysis is carried out using descriptive-analytic methods. The results of this study indicate that socio-cultural thinking in Ibn Khaldun’s view regarding the growth and development (Social-Culture) in an area cannot be separated from the influence of a country, culture, and is also closely related to history . In addition, social phenomena are subject to the laws of development, all of which will lead to modern culture, which is progressing and being transformed into works of art, scince, philoshopy, and literature.